2006
DOI: 10.1186/1471-2407-6-163
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of mRNA expression of β-defensins in basal cell carcinoma

Abstract: Background: Although the human β-defensins hBDs today seem to have diverse functional activities in innate antimicrobial immunity, a few reports also indicated an altered expression of these antimicrobial peptides (AMPs) in tissues of cancers such as oral squamous cell carcinoma. The present work was aimed on the study of hBD gene expression in basal cell carcinoma (BCC) which is the most common cancer in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 15 publications
2
46
0
7
Order By: Relevance
“…Several studies reported increased expression of b-defensins in different tumor tissues (11)(12)(13). Kawsar et al (14) demonstrated expression of hBD2 in malignant tumor lesions, but not in healthy stroma, suggesting that hBD2 may play a role in tumor angiogenesis.…”
mentioning
confidence: 99%
“…Several studies reported increased expression of b-defensins in different tumor tissues (11)(12)(13). Kawsar et al (14) demonstrated expression of hBD2 in malignant tumor lesions, but not in healthy stroma, suggesting that hBD2 may play a role in tumor angiogenesis.…”
mentioning
confidence: 99%
“…Podnoszona jest ich rola nie tylko w progresji, lecz także w supresji nowotworowej, zwłaszcza w przypadku takich AMPs, jak defensyny, LL-37 i grupa białek S100 z psoriazyną na czele. Wykazano związek ludzkiej β-defensyny 1 (hBD-1) z rakiem jasnokomórko-wym nerki, rakiem prostaty i rakiem jamy ustnej [25,26]; psoriazyny z rakiem pęcherza moczowego i rakiem piersi [27]; hBD-1-3 z BCC i ziarniniakiem grzybiastym [28,29]. Ekspresja hBD-2 jest znacząco zmniejszona w zmianach śródpłaskonabłonkowych wysokiego stopnia (ang.…”
Section: Peptydy Przeciwdrobnoustrojowe W Nowotworach Skóryunclassified
“…Gambichler i wsp. [28] stwierdzili istotną zmianę ekspresji hBD-1 i hBD-2 u pacjentów z BCC w porównaniu ze zdrową skórą osób z grupy kontrolnej. Ekspresja genów defensyny hBD-2 w BCC była podobna do ekspresji w dermatozach o podłożu zapalnym, takich jak atopowe zapalenie skóry i łuszczyca.…”
Section: Peptydy Przeciwdrobnoustrojowe W Nowotworach Skóryunclassified
See 1 more Smart Citation
“…Because of the structural and chemical nature diversity of AMPs, also the probability of microbes to resist AMPs is much lower than conventional antibiotics, make them a good candidate for a novel drug with anti bacterial, anti fungal and anti viral properties [48,49]also Anti parasitic activity [50] and AMPs may used in treatment of cancer [51,52,53] and HIV infections [54].…”
Section: Antimicrobial Peptides Therapeutic Applications and Drug Devmentioning
confidence: 99%